Case Report: Atrial myxoma combined with hyperthyroidism in an adolescent with literature review - Hao, Mengjin; Wang, Libo; Ma, Dashi; Guo, Weiying (Frontiers in Oncology, 2023)
The most common primary cardiac tumors in adults are atrial myxomas, with adolescent-onset being uncommon. In this case report, a 15-year-old female was hospitalized with cerebrovascular embolism and later diagnosed with a left atrial myxoma. She had previously shown signs of distal vascular micro thrombosis, including recurring bilateral lower extremity rash, which are crucial for the early diagnosis and differential diagnosis of atrial mucinous neoplasm. We reviewed the various clinical symptoms and diagnostic approaches to identify left atrial mucinous neoplasm. This patient also had a combination of endocrine-related diseases. We reviewed the diagnostic approach for the Carney Complex (CNC) and discussed the role of thyroid disease in diagnosing CNC.